Results Of Surgical Treatment of Patients with Mirizzi Syndrome - Kurbaniyazov Zafar Babazhanovich; Rakhmanov Kosim Erdanovich; Sulaymonov Salim Uzganboyevich; Abdurakhmanov Diyor Shukurillaevich (Periodica Journal, 2022)
Relevance. The results of surgical treatment of 52 patients with cholelithiasis complicated by Mirizzi's syndrome were analyzed . At the same time, type I was detected in 25 patients, type II - 14, type III-8 and type IV - 5. In the preoperative diagnosis of Mirizzi syndrome , MRCP is the most effective, which made it possible to determine the morphological type of this pathology in 54.5%. Tactical and technical aspects of surgical treatment are optimized depending on the type of Mirizzi syndrome.
Keywords: cholelithiasis; Mirizzi syndrome; cholecystectomy; diagnosis